2018
DOI: 10.1002/pts.2407
|View full text |Cite
|
Sign up to set email alerts
|

The influence the image of the product shown on food packaging labels has on product perception during tasting: Effects and gender differences

Abstract: Many food packages on the market show an image of the product contained inside or the ingredients with which the product was produced. During the packaging design process, it is the job of the designer or the marketing team to decide which specific image will be depicted on the packaging. This paper analyses the potential implications of this decision by studying the influence that the visual appearance of the product pictured on the packaging has on the way consumers perceive the product during consumption. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
4
13
0
1
Order By: Relevance
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
“…Finally, most of the Swedish respondents (86%) were willing to pay 6% more for environmentally sustainable packaging (Lindh et al , 2016). Lidón et al (2018) showed a strong positive relationship between the healthy image of a package and the willingness to buy. As such, to depict an image perceived as healthy on a package may increase consumers’ willingness to buy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as a limitation of this work, we can define the absence of real packages/labels, as these also strongly affect the consumers' perception (Lidón, Rebollar, Gil‐Pérez, Martín, & Vicente‐Villardón, ; Tijssen, Zandstra, den Boer, & Jager, ). Therefore, for future research in this area, we suggest evaluating information about these products inserted in simulated labels, to determine ways (phrases, colors, font sizes) to help consumers pay attention to label information and then measure if this effectively impacts the purchase intent of the products.…”
Section: Resultsmentioning
confidence: 99%